Childhood Maltreatment, Mental Well-Being, and Healthy Lifestyle in Patients With Chronic Thromboembolic Pulmonary Hypertension - Lepsy, Nicole; Dering, Madelaine-Rachel; Fuge, Jan; Meltendorf, Tanja; Hoeper, Marius M.; Heitland, Ivo; Kamp, Jan C.; Park, Da-Hee; Richter, Manuel J.; Gall, Henning; Ghofrani, Hossein A.; Ellermeier, Dietmar; et al. (Frontiers in Psychiatry, 2022)
Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is a potentially life-threatening condition associated with high morbidity and mortality. However, advances in medical, surgical and interventional treatment have markedly improved the outcome of patients with CTEPH. Additional factors potentially influencing quality of life (QoL) and outcome in CTEPH are yet to be defined. Child maltreatment is a major risk factor for unfavorable behavioral, mental as well as physical health outcomes and has been associated with decreased QoL. To date, no study assessed the impact of childhood trauma in patients with CTEPH. Methods: Patients with CTEPH were invited to complete the Childhood Trauma Questionnaire (CTQ). Data were compared to prevalence data from the German population. Mental well-being was assessed using the Hospital Anxiety and Depression Scale (HADS) and quality of life was measured using the WHO Quality of Life Questionnaire (WHOQOL). Furthermore, lifestyle factors and physical health parameters were studied. Logistic regression analysis was used to investigate a possible impact of child maltreatment on markers of disease severity. Results: 107 patients with CTEPH completed the CTQ. These patients reported higher rates of emotional abuse and physical abuse and emotional neglect compared to the German population while rates of physical neglect and sexual abuse did not differ between patients and German population with prevalence of 20.6% for emotional abuse, 20% for physical abuse, 22% for emotional neglect, 46% for physical neglect and 6% for sexual abuse in patients with CTEPH. Higher CTQ scores were associated with anxiety symptoms as well as negatively associated with QoL. No direct impact of childhood trauma on CTEPH severity was found. Conclusion: We found a higher rate of child maltreatment in patients with CTEPH in comparison to the German population. Correlations suggest moderate associations between CTQ scores and mental health and QoL. Child maltreatment had no significant impact on disease severity. Further investigation on proper interventions to support affected patients is needed.